2018
DOI: 10.1021/acs.jpcc.7b10452
|View full text |Cite
|
Sign up to set email alerts
|

Combined TPD and XPS Study of Ligation and Decomposition of 1,6-Hexanedithiol on Size-Selected Copper Clusters Supported on HOPG

Abstract: Ligation and decomposition of 1,6-hexanedithiol on copper clusters have been studied by means of temperature-programmed desorption (TPD) and X-ray photoelectron spectroscopy (XPS). Copper cluster anions were first made via magnetron sputtering, then size selected and soft landed into a frozen matrix of 1,6-hexandithiol on highly ordered pyrolytic graphite (HOPG) maintained at 100 K. After warming up to 298 K, a combination of TPD and XPS were performed to characterize the newly deposited sample. TPD data shed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…It should be mentioned that Cu 2+ in bare (CuO) 80 clusters can be reduced completely to Cu 1+ upon annealing to 200 °C under UHV (Figure b). Moreover, multiple studies have shown that lattice oxygen in CuO can participate in dissociative adsorption and oxidative decomposition processes at room temperature and elevated temperatures for many organic molecules such as DMMP, methanol, , and alkanethiols. , Therefore, the disappearance of low binding energy feature can be ascribed to the oxidative effects on potential atomic phosphorus from the activated lattice oxygen within (CuO) 80 as well as the loss of satellite feature of Cu 3s due to reduction of Cu 2+ into Cu 1+ upon heating to 200 °C.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be mentioned that Cu 2+ in bare (CuO) 80 clusters can be reduced completely to Cu 1+ upon annealing to 200 °C under UHV (Figure b). Moreover, multiple studies have shown that lattice oxygen in CuO can participate in dissociative adsorption and oxidative decomposition processes at room temperature and elevated temperatures for many organic molecules such as DMMP, methanol, , and alkanethiols. , Therefore, the disappearance of low binding energy feature can be ascribed to the oxidative effects on potential atomic phosphorus from the activated lattice oxygen within (CuO) 80 as well as the loss of satellite feature of Cu 3s due to reduction of Cu 2+ into Cu 1+ upon heating to 200 °C.…”
Section: Discussionmentioning
confidence: 99%
“…TPD can offer evidence on the evolution of gaseous products during the temperature ramping, while XPS acquired after heating the sample to several critical temperatures can elucidate residual species on the surface. Our group has successfully applied this method to shed light on the decomposition mechanism of several organic molecules, including DMMP, on size-selected metal and metal oxide clusters. , Similarly, the decomposition process of DMMP on Cu 100 and (CuO) 80 clusters has been analyzed and compared via combined XPS and TPD in this study. As is shown in Scheme , a plausible DMMP decomposition scheme is presented with all the surface species and gaseous products described in the previous sections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1b). The size-selected Pt n (n = 4, 7-10, 15) clusters on TiO 2 (110) surfaces were scanned using an ultrahigh-vacuum STM with a carbon nanotube tip. The clusters smaller than Pt 7 laid flat on the surface with a planar structure.…”
Section: Stmmentioning
confidence: 99%